Incorpórese un numeral al artículo 112 del Código de la Niñez y Adolescencia, en donde se sancione a la persona que teniendo la patria potestad o tenencia, no permita el régimen de visitas - Cevallos Betancourt, Jorge Enrique (2015)
The present investigation is headed on the social consequences that exist in the world to leave tenure under custody and they are not allowed visitation. There is a big difference is the desire that people respect and form a home of harmony, affection and love that parents living with their children and if they do not. In Ecuador, in the city of Loja, less tenure brings social consequences that directly affect the children, since they lack of love, affection, love, coexistence, among others. In this topic examined what the behavior of the different actors in the legal work, and what was their contribution against the need to establish penalties for the person who holds the power or possession homeland, does not allow visitation provisions judgment, the reforms to be implemented will be established with major doctrinal proposals. Decomposed some phases of procedures, establish different treatment who have had judgments by Country information which allows us to differentiate the treatment by the legislator has not been the same, to detect and find the causes that determine, for that constitutional principles do not reach the desired position, you will not parciality to any party because it will respect their rights so there is a loophole around the penalty for breach of visitation established Judicial resolution of parental authority or tenure is so keeping the vision guarantor of the rights of all citizens by the Constitution of the Republic of Ecuador paragraph 16 of Art. 83 gives the following duties and responsibilities of Ecuadorians attend feed educate their children however most cases trials are heard in the courts of childhood and adolescence the right to alimony precautionary measures as are prohibited from leaving the country, embargo essential to life, personal urgency goods is guaranteed; in judgments Custody visitation which is not fulfilled is also fixed. As it is proposed to incorporate in Art. 112 of the Code of Childhood and Adolescence sanctions, so changes that have occurred, such as in the physical infrastructure of the judiciary stands, implementation of computer systems, allowing for better accountability to society, judicial units at par decisions of the Courts of Justice on specific issues, to demonstrate that the performance of judges is divorced many times their powers-duties, and which solutions could be comparing them with legal bodies in other countries, all of which seeks to demonstrate that our legislation needs to implement sanctions that body of law to enforce judicial decisions